Rancang Bangun Phonocardiograf Berbasis Labview - Ramdani Febrian; Budi Sumanto (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2020)
The aim of this research is to develop a phonocardiograph system to display the signal and information form of the human heart sound examination. The analytical method applied is to use the Fast Fourier Transform (FFT) to determine the frequency of responses of human heart sound signals by using Labview software. The results obtained indicate the system able to display the signal shape of the heart sound, based on ten respondents whose data are taken shows the range of heart sound frequencies is in the range of 145 to 225 Hz with a duration of 81 to 120 bpm. Keywords: Phonocardiograph, FFT, Labview